2007
DOI: 10.1074/jbc.m610978200
|View full text |Cite
|
Sign up to set email alerts
|

HCN2 and HCN4 Isoforms Self-assemble and Co-assemble with Equal Preference to Form Functional Pacemaker Channels

Abstract: Hyperpolarization-activated cyclic nucleotide-modulated (HCN) "pacemaker" channel subunits are integral membrane proteins that assemble as tetramers to form channels in cardiac conduction tissue and nerve cells. Previous studies have suggested that the HCN2 and HCN4 channel isoforms physically interact when overexpressed in mammalian cells, but whether they are able to co-assemble and form functional channels remains unclear. The extent to which co-assembly occurs over self-assembly and whether HCN2-HCN4 heter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
40
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 39 publications
(54 reference statements)
5
40
0
Order By: Relevance
“…This conclusion is in accord with previous immunohistochemical findings showing that HCN2 and HCN4 are co-localized in (embryonic) mouse heart (22). The results here importantly extend these earlier findings with the demonstration that HCN2 and HCN4 can be co-immunoprecipitated from heart.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This conclusion is in accord with previous immunohistochemical findings showing that HCN2 and HCN4 are co-localized in (embryonic) mouse heart (22). The results here importantly extend these earlier findings with the demonstration that HCN2 and HCN4 can be co-immunoprecipitated from heart.…”
Section: Discussionsupporting
confidence: 93%
“…together with heteromeric HCN2: HCN4 channels, in the myocardium (22). Consistent with previously reported findings (15,22), results are also presented here showing that both HCN2 and HCN4 can form homomeric HCN channels in heterologous cells when expressed alone and that the time-and voltage-dependent properties of the (homomeric) currents are distinct (Fig.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The number of HCN channels on the cell surface is a critical determinant of beating frequency in cardiac conduction tissue. HCN isoforms and HCN-mediated currents (I h ) are upregulated in the embryonic and neonatal ventricle (24,45,53,56), in the neonatal sinoatrial node (1), and in beating embryonic stem cells during development in culture (27,36,40,41). However, the factors that determine HCN channel supply at the cell surface during cardiac development have been studied in only a limited fashion.…”
mentioning
confidence: 99%
“…I f is encoded by both HCN2 and HCN4 in the ventricles (Shi et al, 1999;Stillitano et al, 2008). Recent evidence has shown that they can form heteromeric channels in vitro and in vivo producing an I f with physiological activation (Much et al, 2003;Whitaker et al, 2007;Zhang et al, 2009). The respective roles for I f and I K1 in the induced ventricular pacemaker activity have recently been evaluated in the guinea pig left ventricular myocytes overexpressing either HCN1-ΔΔΔ or Kir2.1 (Chan et al, 2009).…”
Section: Enhancement Of I Fmentioning
confidence: 99%